CLIMATE CHANGE IMPACT ON WATER RESOURCES AVAILABILITY AND HYDROPOWER PRODUCTION IN SARAWAK, MALAYSIA - HUSSAIN, MUBASHER (2018)
This research focused on potential impact of climate change on water resources availability and hydropower production in Sarawak state of Malaysia. Future precipitation over Rajang River Basin (RRB) and Batang Ai Catchment (BAC) was projected using General Circulation Models (GCMs) from Coupled Model Intercomparison Project Phase 5 (CMIP5). Based on the capability to simulate the historical precipitation, three most suitable GCMs (ACCESS1.0, ACCESS1.3, and GFDL-ESM2M) were selected and their mean ensemble (B3MMM) was used to simulate the future precipitation over the study areas